The therapeutic impacts of environmental design interventions on wellness in clinical settings: A narrative review - Iyendo, Timothy Onosahwo; Uwajeh, Patrick Chukwuemeke; Ikenna, Ezennia Stephen (Elsevier Sci Ltd, 2016)
Purpose: The aim of this review is to document the role of physical environmental factors in clinical environments and their impact on patients and staff wellness with a particular focus on physical and mental healthcare. Methods: Data sources comprised relevant English language articles and the results of literature search of ISI Web of Knowledge, PubMed, Scopus, ProQuest Central, MEDLINE, and Google. Results: Incorporating physical environmental factors into hospital design can facilitate better user satisfaction, efficiency and organisational outcomes. Many of the design interventions convey positive distractions for patients and staff, in terms of views of pleasant outside vistas, soothing sound, artwork and music. Conclusions: Well-designed physical settings play an important role in the healing process of, patients in health care facilities. The challenge then is to fully understand that role in the ecological context of health care. Other contributors are possible and should be explored in further research. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Clinical settings; Design factors; Healing environment; Physical environment; Therapeutic sound; Wellness